Brown's syndrome: The individual forms and their treatment (including expander of own construction) - Krásný, Jan (Czech and Slovak Ophthalmology, 2017)
Aim: Familiar with the treatment of various forms of Brown‘s syndrome and its success. To document preparation of the expander own design. Material and methods: In the years 1996–2016 was operated 33 pacients with congenital Brown‘s syndrome by using an extension of its tendon expander at the Eye Clinic of the University Hospital Vinohrady in Prague. Author proves photographs preparing expander own design and modified surgical technique. It was also operated on 10 patients for accompanying Y-exotropia. Eleven patients with acute form of Brown´s syndrome in the pulley of upper oblique muscle applied Betamethasoni. Results: The using expander own design – non-resorbable Ethibond 5–0 cauted silicone cannula – held at congenital form of Brown‘s syndrome, without a weighty complication or its exclusion in the period. The result of the performance was determined age of patients at the time of implantation of the expander. Preschoolers postoperative condition was fully compliant, this expander standardized vertical mobility. The vertical alignment motility is reduced with advancing age, especially in adulthood. Optimal surgical procedures at Y-exotropia were antepozice with recession of the inferior oblique muscle possibly supplemented by retroposition ipsilateral external rectus. The application efficiency of Betamethasoni for acute form of Brown´s syndrome in the pulley of upper oblique muscle was successful in only two weeks after the initial symptoms vertical diplopia. Conclusion: Expander own design which represented non-resorbable Ethibond cauted silicone cannula was very effective in dealing with congenital form of Brown‘s syndrome. The application of glucocorticoids in the pulley of upper oblique muscle should always be a quantity result.
Keywords: výsledek terapie; Young Adult; kanyla; Ocular Motility Disorders; Child, Preschool; protézy a implantáty; okulomotorické svaly; mladý dospělý; Brownův syndrom; Child; dítě; Adult; dospělí; oftalmologické chirurgické výkony; Severity of Illness Index; betamethason; Treatment Outcome; Oculomotor Muscles; předškolní dítě; expander; lidé; Humans; exotropie; Cannula; Betamethasone; Prostheses and Implants; poruchy hybnosti oka; stupeň závažnosti nemoci; Ophthalmologic Surgical Procedures; lidé středního věku; Ethibond; Middle Aged; Exotropia